2003
DOI: 10.1073/pnas.1936166100
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enhanced GFP-based dual-color reporter to facilitate genetic screens for the recovery of mutations in mice

Abstract: Mutagenesis screens to isolate a variety of alleles leading to null and non-null phenotypes represent an important approach for the characterization of gene function. Genetic schemes that use visible markers permit the efficient recovery of chemically induced mutations. We have developed a universal reporter system to visibly mark chromosomes for genetic screens in the mouse. The dualcolor reporter is based on a single vector that drives the ubiquitous coexpression of the enhanced GFP (EGFP) spectral variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Long-term separated blastomeres preferentially contribute to the trophectoderm of the blastocyst To determine whether the observed gene expression patterns observed correlate with the developmental behavior of LS blastomeres, we aggregated separated blastomeres, from a transgenic mouse that abundantly expresses green fluorescent protein (GFP) in each cell (Frank et al, 2003), with zona-free intact eight-cell stage embryos (i8C) (Fig. 4A).…”
Section: Research Articlementioning
confidence: 99%
“…Long-term separated blastomeres preferentially contribute to the trophectoderm of the blastocyst To determine whether the observed gene expression patterns observed correlate with the developmental behavior of LS blastomeres, we aggregated separated blastomeres, from a transgenic mouse that abundantly expresses green fluorescent protein (GFP) in each cell (Frank et al, 2003), with zona-free intact eight-cell stage embryos (i8C) (Fig. 4A).…”
Section: Research Articlementioning
confidence: 99%
“…It has been suggested that the GFP-based fluorescent coat color markers should offer significant benefits when applied to various screening strategies to recover induced mutations in the mouse (Frank et al, 2003;Klysik, 2002). Consistently, the EGFP knocked-in strain described in this paper, in combination with previously generated K14-agouti tagged Trp53-Egfr inversion, should facilitate tracing of the tagged chromosome in genetic crosses to uncover recessive phenotypes on mouse chromosome 11.…”
Section: Discussionmentioning
confidence: 99%
“…Large segmental inversions, or balancers (Frank et al, 2003;Justice et al, 1999;Kile et al, 2003;Klysik et al, 2003Klysik et al, , 2004Rinchik, 2000), constitute effective tools that allow one to address ∼2% of the genome in a single mutagenesis experiment. Balancers were first observed in Drosophila melanogaster stocks causing self-perpetuating maintenance of lethal mutations located on homologous chromosomes (Muller, 1918).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative strategy uses radiation mutagenesis to induce deletion complexes surrounding an integrated drug selection cassette (You et al 1997; Thomas et al 1998). Furthermore, the K‐14‐agouti transgene or enhanced green fluorescent protein (EGFP) based transgenic strategies can serve as visible markers to couple with the chromosomal aberration resources (Zheng et al 1999; Frank et al 2003). Thus, marked, regionally directed mutagenesis screens – once restricted to deletion complexes surrounding classic coat colour and dysmorphology loci – can now be applied across the genome.…”
Section: Mutagenesis Screens In the Mouse Taking Advantage Of A Regimentioning
confidence: 99%